Fostering Post‐Wildfire Research. Issue 4 (28th January 2014) - Moody, John A.; Martin, Deborah A.; Robichaud, Peter R.; Shakesby, Richard A.
<x xml:space="preserve">Abstract</x> Post‐wildfire research is challenging because wildfires frequently burn in complex mountainous terrain, and responses are frequently driven by additionally complex mesoscale (on the order of 1 to 10, 000 square kilometers), spatially and temporally variable rainfall. Thus, responses are highly variable spatially and transient in nature, producing shallow, unsteady overland flow on hillslopes (1 centimeter or less) and unsteady, non‐uniform flow in channels.